Behaviour of Tensile Testing of X-120M Steel from Plate to Line Pipe Due to Bauschinger Effect (Global Journal of Science Frontier Research, 2012)
The X-120M ‘V-Nb-Ti-B’ micro alloyed steel of bainitic microstructure used in the experiment having high dislocation density. High dislocation density was due to the nature of Thermo Mechanical Controlled Processing and Accelerated Cooled rolling to achieve the strength level of X- 120 ksi. During the cold forming and mechanical expansion, the deformation occurred which reversed the strain. The reversal of strain leads to increase in yield strength to ultimate tensile strength ratio in transverse direction. The tensile test has been performed for steel plate as well as on line pipe formed in longitudinal and transverse of rolling of the plate and longitudinal and transverse direction of the line pipe axis before and after the mechanical expansion of the line pipe. The yield strength and ratio of yield strength to ultimate tensile strength in transverse direction is more after mechanical expansion of the line pipe as compared before expansion transverse yield strength because of the bauschinger effect. In longitudinal direction the results remains the same because the hoops stresses developed in transverse direction with respect to the axis of the line pipe.
Keywords: Bauschinger Effect; Thermo Mechanical Controlled Processing and Accelerated Cooled rolling; Yield Strength and Ultimate Tensile Strength